Design of a Compression Training System using a Mechanical Chest Response Model - ERWANI MERRY SARTIKA; KALYA ICASIA; CHE-WEI LIN; FEBRIAN SETIAWAN (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Cardiopulmonary Resuscitation (CPR) is an emergency medical procedure performed on patients experiencing cardiac arrest. In this study, the mechanical response of the human chest during CPR compression is modeled using a spring–damper system. To better represent the actual chest response, the damper is regulated using a control system integrated into a CPR training model. The overall system design, including the human chest response model and the control system, utilizes a spring mechanism, an HC-SR04 ultrasonic sensor for measuring compression depth, LED indicators, and a buzzer as feedback components. A user interface (UI) is also developed to operate and monitor the entire system. The damping setpoint is designed with a variable viscosity constant that changes according to the chest compression depth, approximating the characteristics of the human chest response. A PID controller with gains , , and is implemented. The system produces an output response with a settling time of 5 seconds and a total error of 0.4457. The calculated compression force ranges from 320 to 420 N for compression depths of 4–5.5 cm.